2018
DOI: 10.1038/s41523-018-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of PET and MRI radiomic features for decoding breast cancer phenotypes and prognosis

Abstract: Radiomics is an emerging technology for imaging biomarker discovery and disease-specific personalized treatment management. This paper aims to determine the benefit of using multi-modality radiomics data from PET and MR images in the characterization breast cancer phenotype and prognosis. Eighty-four features were extracted from PET and MR images of 113 breast cancer patients. Unsupervised clustering based on PET and MRI radiomic features created three subgroups. These derived subgroups were statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 37 publications
4
59
0
Order By: Relevance
“…Other studies have focused on building radiomic models predictive of a clinical endpoint, such as survival or response to therapy 46,47 . To date, only a few studies have investigated the functional links between radiomics and other omics data 26,27,48 . In 2007, Segal et al have suggested that gene expression profiles could be reconstructed using "image traits" derived from CT scans in hepatocarcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on building radiomic models predictive of a clinical endpoint, such as survival or response to therapy 46,47 . To date, only a few studies have investigated the functional links between radiomics and other omics data 26,27,48 . In 2007, Segal et al have suggested that gene expression profiles could be reconstructed using "image traits" derived from CT scans in hepatocarcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The next step is to specify (or segment) the ROI, from which radiomics features are computed. ROIs are specified to limit the spatial extents of the analysis and can be specified manually, semi-automatically, or automatically (16,17). Among the methods of tumor segmentation, automated or semi-automated methods have been reported to be superior to manual methods for segmenting the tumor (18,19).…”
Section: Specification Of Roismentioning
confidence: 99%
“…To rationalize the number of bins, a statistical formula such as the Freedman-Diaconis rule could be applied. Existing breast imaging studies reported the entropy, mean, minimum, and maximum as important features (17). These features do not consider the spatial neighborhood information of the voxels.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Non-invasive image-derived biomarkers can also be generated from PET radiomics according to the intensity of the pixels, their associated parameters, and their positions (138). Based on the clinical application of PET-based techniques, several studies have focused on the clinical and technical feasibility of applying PET radiomics to diagnosis (139,140), staging (141)(142)(143), pathological characterization (17,18), NAC response (18,(144)(145)(146), and outcome prediction (147,148) in breast cancer. However, the difficulty in detecting the edges of breast lesions using CT limits the PET/CT in identifying the breast tumor and the alignment of the imaging modalities (141).…”
Section: Pet Radiomicsmentioning
confidence: 99%